Development of the perceptions of preventable adverse events assessment tool (PPAEAT): measurement properties and patients' mental health status. (3rd April 2021) - Keller, Franziska Maria; Derksen, Christina; Kötting, Lukas; Schmiedhofer, Martina; Lippke, Sonia
Abstract: Background: Patient-centered care and patient involvement have been increasingly recognized as crucial elements of patient safety. However, patient safety has rarely been evaluated from the patient perspective with a quantitative approach aiming at making patient safety and preventable adverse events measurable. Objectives: The objectives of this study were to develop and evaluate the psychometric properties of a questionnaire assessing patient safety by perceived triggers of preventable adverse events among patients in primary health-care settings while considering mental health. Methods: Two hundred and ten participants were recruited through various digital and print channels and asked to complete an online survey between November 2019 and April 2020. Exploratory factor analysis was performed to identify domains of triggers of preventable adverse events affecting patient safety. Furthermore, a multi-trait scaling analysis was performed to evaluate internal reliability as well as item-scale convergent–discriminant validity. A multivariate analysis of covariance evaluated whether individuals below and above the symptom threshold for depression and generalized anxiety perceive triggers of preventable adverse events differently. Results: The five factors determined were information and communication with patients, time constraints of health-care professionals, diagnosis and treatment, hygiene and communication among health-care professionals, and knowledge and operational procedures. The questionnaire demonstrated a good total and subscale internal consistency (α = 0.90, range = 0.75–0.88), good item-scale convergent validity with significant correlations between 0.57 and 0.78 ( P   < 0.05; P   < 0.01) for all items with their associated subscales, and satisfactory item-scale discriminant validity between 0.14 and 0.55 ( P   > 0.05) with no significant correlations between the items and their competing subscales. The questionnaire further revealed to be a generic measure irrespective of patients' mental health status. Patients older than 50 years of age perceived a significantly greater threat to their own safety compared to patients below that age. Conclusion: The developed Perceptions of Preventable Adverse Events Assessment Tool (PPAEAT) exhibits good psychometric properties, which supports its use in future research and primary health-care practice. Further validation of the PPAEAT in different settings, languages and larger samples is needed. The results of this study need to be considered when assessing patient safety in the context of health-care research.